Crosslink density and mechanical property evolution during the curing of polyurethane-urea/sodium silicate hybrid composites. (February 2022) - Sun, Yong; Yu, Anqi; Liang, Yuntao; Wang, Gang; Song, Shuanglin; Lu, Wei; He, Zhenglong; Meng, Shaocong
In order to understand the evolution of the structure–property relationship between the crosslink density and mechanical properties of polyurethane-urea/sodium silicate (PU/SS) hybrid composites, a series of PU/SS composites with 2.5 wt% organofunctional silanes and pure PU/SS composites are investigated at different curing time. Mechanical properties, the fracture surface morphology, and thermo-mechanical properties of these PU/SS composites are characterized by electron omnipotence experiment machine, scanning electron microscope, and dynamic mechanical analysis (DMA), respectively. The mechanical test results show the strength and fracture toughness of the PU/SS composites first increase and then stabilize during cure, and the modification leads to PU/SS composites with significantly higher mechanical properties. Further, the morphology of fractured samples also reveals that the longer curing time and the modification of the PU/SS composites means a higher curing degree. Moreover, the increase in the crosslink density calculated from the DMA tests quantitatively confirmed the positive influence of the curing time and the modification in enhancing mechanical properties. In addition, it is also found that the mechanical properties of the PU/SS composites not only depend on the crosslink density but also on the well-dispersed hybrid PU/SS system.